2020
DOI: 10.3354/meps13438
|View full text |Cite
|
Sign up to set email alerts
|

Climate-change impacts and fisheries management challenges in the North Atlantic Ocean

Abstract: Climate-induced changes in the world’s oceans will have implications for fisheries productivity and management. Using a model ensemble from the Fisheries and Marine Ecosystem Model Intercomparison Project (Fish-MIP), we analyzed future trajectories of climate-change impacts on marine animal biomass and associated environmental drivers across the North Atlantic Ocean and within the Northwest Atlantic Fisheries Organization (NAFO) convention area and evaluated potential consequences for fisheries productivity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 79 publications
(120 reference statements)
1
8
0
Order By: Relevance
“…The model approach of Kleisner et al (2017) supported the observed poleward shift of thermal fish habitats. This was also shown in the ensemble model study of Bryndum-Buchholz et al (2020) with a fish biomass increase in Arctic regions and a decrease in tropical regions. The fish collapse in the Northwest Atlantic was explored with statistical models, which revealed that the reason was a mixture of fishing and environmental impacts (Dempsey et al, 2018).…”
Section: Finfishsupporting
confidence: 71%
“…The model approach of Kleisner et al (2017) supported the observed poleward shift of thermal fish habitats. This was also shown in the ensemble model study of Bryndum-Buchholz et al (2020) with a fish biomass increase in Arctic regions and a decrease in tropical regions. The fish collapse in the Northwest Atlantic was explored with statistical models, which revealed that the reason was a mixture of fishing and environmental impacts (Dempsey et al, 2018).…”
Section: Finfishsupporting
confidence: 71%
“…While individual marine ecosystem models (MEMs) have explored climate impacts on ocean ecosystems, the Fisheries and Marine Ecosystem Model Intercomparison Project (Fish-MIP) compares models produced by different modelling groups into standardized ensemble projections 11 . Fish-MIP has explored a range of topics, including global 12 and regional 13 15 changes over the coming century and their potential socioeconomic consequences 8 .…”
Section: Mainmentioning
confidence: 99%
“…Predicting how climate change may alter the abundance and distribution of marine species is an important application of species distribution models (SDMs). The approach is rapidly expanding in the field of marine ecology (Freer et al, 2017;Robinson et al, 2017;Melo-Merino et al, 2020) and is increasingly being used to guide adaptive fisheries management, marine conservation plans, impact assessments, and policy decisions (Freer et al, 2017;Tittensor et al, 2019;Bryndum-Buchholz et al, 2020a). Species distribution forecast models combine known biological-environmental relationships with downscaled oceanographic models to project species range shifts under one or more Representative Concentration Pathways (RCPs) of greenhouse gas concentration trajectories.…”
Section: Introductionmentioning
confidence: 99%